EFFECTS OF MOLASSES SUPPLEMENTATION IN COMMERCIAL FEEDS ON THE GROWTH PERFORMANCE OF SALINE TILAPIA (Oreochromis niloticus): PENGARUH SUPLEMEN MOLASES DALAM PAKAN KOMERSIAL TERHADAP PERTUMBUHAN IKAN NILA SALIN (Oreochromis niloticus) - Permatasari, Indah; Nurhatijah, Nurhatijah; Azhar, Rossy (PT. ROCE WISDOM ACEH, 2025)
This study aimed to evaluate the effects of molasses supplementation in commercial feed on the growth performance of saline tilapia (Oreochromis niloticus) fry. A Completely Randomized Design (CRD) with four treatments and five replications was employed: A (control), B (10 mL molasses), C (20 mL molasses), and D (30 mL molasses). Growth performance parameters included specific growth rate, absolute weight gain, length gain, and survival. Results demonstrated that molasses supplementation had a significant effect (p < 0.05) on all parameters. Treatment C (20 ml) achieved the best performance, with a specific growth rate of 1.62%, an absolute weight gain of 1.24 g, and a survival rate of 76%. In contrast, Treatment D (30 ml) yielded the lowest growth performance, indicating that excessive molasses supplementation reduced feed palatability and negatively affected culture outcomes. These findings suggest that supplementation with 20 ml of molasses provides the optimal dosage to enhance the growth and survival of saline tilapia fry.